![g(x)=-2x-2](https://img.qammunity.org/2023/formulas/mathematics/college/967agpimiwt1d02ug9xsza128tdjg5qw4b.png)
1) Given that the g(x) function is the result of transforming f(x) by shifting to the right 2 units and reflecting across the y-axis, we can tell that:
2) So, let's shift to the right 2 units:
g(x)=f(x-2)
![g(x)=f(x)=2(x-2)=2x-2](https://img.qammunity.org/2023/formulas/mathematics/college/ql1mqgb3y2dya31qx11eopwfcfrqwqj5e5.png)
3) Now, let's reflect it across the y-axis. To do that let's multiply by -1
![g(x)=-2x-2](https://img.qammunity.org/2023/formulas/mathematics/college/967agpimiwt1d02ug9xsza128tdjg5qw4b.png)